Analisis Yuridis terhadap Tindak Pidana Tanpa Hak Menguasai Senjata Tajam dan Perbuatan Pengancaman terhadap Orang Lain: (Studi Kasus Putusan Nomor 1807/Pid.Sus./2023/PN Lbp) - Saidfuddin Saidfuddin; Dani Sintara (Jurnal Hukum dan Sosial Politik, 2024)
A weapon is a tool used to injure, kill, or destroy an object. Weapons can be used to attack or defend oneself, and also to threaten and protect. The purpose of this study is to determine the Legal Analysis of Criminal Acts Without the Right to Control Sharp Weapons and Threatening Acts Against Others (Case Study of Decision Number 1807/Pid.Sus./2023/PN Lbp). The type of research used in this study is empirical legal research, namely legal research conducted by directly examining or secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Data collection methods are techniques or methods that can be used by researchers to collect data. Techniques in designating an abstract word that is not manifested in objects, but can only be seen in its use through: questionnaires, interviews, observations, exams (tests), documentation, and others. Based on the results of the study, Article 2 paragraph (2) of Emergency Law Number 12 of 1951 can be seen exceptions to the provisions of the article above which are given by this law. Sharp weapons used for agriculture or for household chores or other work. From the interview results, it can be explained that one of the driving factors for carrying sharp weapons is if you want to commit theft. This is because stolen objects are usually in a place of security by the owner of the goods, so thieves need certain tools, especially sharp weapons, to be able to more easily control the objects or goods they want to steal. In Decision Number 1807/Pid.Sus./2023/PN Lbp, the Panel of Judges explained that all elements of Article 2 paragraph (1) of Emergency Law Number 12 of 1951 have been fulfilled. One of the elements that is considered is "whoever", which according to Memorie van Toelichting refers to a legal subject who can be held accountable. In this context, the Defendant clearly meets the requirements as a perpetrator of a crime. This is confirmed by the existence of evidence showing that the Defendant did not have a permit to carry the sharp weapon. Based on the results of the research that has been conducted, it can be concluded that: What factors encourage the occurrence of criminal acts without the right to carry sharp weapons and acts of threatening others (Case Study of Decision Number 1807 / Pid.Sus. / 2023 / PN Lbp) From the results of the interview above, it can be explained that criminal groups are the main perpetrators who are often involved in carrying sharp weapons. The main reason criminal groups carry sharp weapons is to be used in criminal acts, such as theft.